The end of averages for marketing budgets - Tavassoli, Nader T.; Moorman, Christine (MIT Sloan Management Review, 2023)
For marketers, budget averages have long equaled spending power - or vulnerability. When budgets are below average, CMOs seek more funding. When budgets are above average, CFOs seek to tighten the belt. However, the authors argue that marketing-budget averages can be misleading. Here's what they learned about how marketing budgets break down across several more-specific factors - and how to make better comparisons - through their analysis of data from The CMO Survey.
Reprint #65234. - Includes bibliographical references
Keywords: Marketing -- Management; Budget in business; Marketing; Gestion; Gestion budgétaire